Hots FOR TEACHING AND LEARNING IN A TEACHER EDUCATION UNIVERSITY - M. Pillay, Logeswari Arumugam; Singh, Charanjit Kaur Swaran; Yunus, Melor Md. (International Journal of Psychosocial Rehabilitation, 2020)
Abstract: Purpose of the study: This study investigated the implementation of higher order thinking skills (HOTs) in the classroom and the processes involved in the teaching and learning of HOTs to determine the strategies that the TESL teacher educator (TE) employed in implementing the teaching and learning of HOTs.Methodology: This study utilized a qualitative approach to obtain the TE’s experiences in the natural context of implementing HOTs. Fourteen lessons of the semester 5 and 6 of the TESL programme involving one TE and twenty-seven STs were observed and analysed inductively for dominant issues and categories. The environment of the classroom and the teaching and learning process through various methods have been described as being highly interactive, supportive of critical and creative thoughts, as well as evaluative and analytical. These are key attributes that influenced the implementation of HOTs in the TESL classroom, which established the successful use of HOTs.Main Findings: The findings of this study would give an insight to teacher educators training TESL student teachers in the teaching and learning of thinking, more specifically in incorporating HOTs in their daily lectures through the teaching and learning planned and designed for teacher education. It would also help teacher educators to understand the specific strategies in the aspect of implementing HOTs for teaching and learning amongst student teachers. This study would also be an eye-opener to the TESL teacher educators as it will inform them on what are the factors that influence the implementation of HOTs for teaching and learning in the TESL teacher education programmes. Having knowledge of the factors that influence the implementation of HOTs can help teacher educators to be well equipped with the learning strategies, learning environment and learning activities that promote the teaching and learning of HOTs in their classroom.Applications: The pedagogy styles in this study are basically the best practices and strategies used by the teacher educator in this study to implement HOTs. When the student teachers undergo learning based on HOTs, they are bound to develop skills which enable them to reflect upon the provided topic of learning. Not only that, the student teachers are able to develop their own perceptions about the topic. While implementing HOTs based learning, the student teachers were motivated to question the topic of learning. It was possible for them to develop their questioning skills and enhance reasoning and aptitude skills.Novelty of this study: According to Malini & Kaur (2014), there is scant research which has attempted to investigate how teachers construct pedagogical content knowledge to teach HOT skills. In fact, very few studies have been carried out to investigate how teachers construct the pedagogical content knowledge for teaching language skills by integrating HOTs in Malaysian secondary ESL classrooms. Having said this, there are no studies carried out to investigate teacher educators’ practices for implementing HOTs in the TESL teacher education programmes in Malaysia.